The effect of temperature and other factors on plastics and elastomers - McKeen, Laurence W. (PDL handbook series, 2008)
This book is an update to the first edition compiled and published in 1990 by William Woishnis. A lot has changed in the field since 1990 and a lot has not changed. There are new plastic materials. There has been a huge turnover in ownership of plastics producing companies. There has been a lot of consolidation, which of course means discontinued products. Thus, this update is much more extensive than the usual "next edition." It has been reorganized from a chemistry point of view. Plastics of similar polymer types are grouped into nine chapters. Each of these chapters includes an introduction with a brief explanation of the chemistry of the polymers used in the plastics. An extensive first chapter has been added as an introduction that summarizes the chemistry of making polymers, the formulation of plastics, testing and test methods, and plastic selection.